A multiscale model of cerebral autoregulation. (September 2021) - Tong, Zheng; Catherall, Mark; Payne, Stephen J.
Highlights: A novel multiscale model of cerebral autoregulation with compartment of Nitric Oxide is established. The model is validated using a range of experimental data from the literature, both steady-state and dynamic. NO appears to play a key role in determining the baseline steady-state arteriolar radius. NO plays a largely insignificant role in dynamic cerebral autoregulation due to its saturation. Abstract: The mechanism of cerebral autoregulation ensures a continuous and sufficient blood supply to the brain to maintain normal function in the presence of changes in blood pressure. Impaired cerebral autoregulation is implicated in a range of brain diseases. We thus present here a multiscale model of cerebral autoregulation to provide a more detailed basis for a better understanding of the mechanisms behind impaired autoregulation. This model is built around a model of single arteriole, which includes a model of Nitric Oxide (NO) transport, the myogenic response, and a 4-state kinetic model coupled to a mechanical model of the vessel wall. In particular, the NO component of the model is added here to better understand the interaction mode between NO and the myogenic response, since the role of NO, the recognized effective vasodilator, is poorly understood in this context. This vessel model is then integrated within a model of the full-brain vasculature. The model is validated using a range of experimental data from the literature, both steady-state and dynamic. The model is able to predict the response of the arteriole to changes in both driving pressure and baseline pressure, indicating that the model captures well the balance between the myogenic and metabolic mechanisms. We next plan to examine the ways in which impaired autoregulation is manifested in different patient groups, potentially leading to improved therapy.